Large Reduction in Volume with the Intensive Treatment of Lymphedema: Reduction of Fluids? - Pereira de Godoy, Jose Maria; Gonçalves, Isabella Pereira; Barufi, Stemarys; Godoy, Maria de Fátima Guerreiro (International Journal of Angiology, 2012)
The aim of this study is to report on the intensive treatment of lymphedema of the legs demonstrating a large reduction in volume in a short period of time. The case of a 29-year-old female patient, who developed the most serious form of lymphedema, associated with verrucosities of the leg and genitalia is reported. Elephantiasis evolved after surgery and radiotherapy. The patient was treated at the Clinica Godoy in Sao Jose do Rio Preto, Brazil using an intensive course of treatment. Baseline and then daily evaluations of the leg perimeter and body weight were performed during treatment. Intensive treatment for 8 hours daily was performed on an outpatient basis using manual and mechanical (RAGodoy device, São Jose do Rio Preto, São Paulo-Brazil) lymph drainage and the continuous use of a compression garment made of a cotton-polyester textile and adjusted every 3 hours. A reduction of 31 kg was seen in 10 days (over 2 weeks); in the first few days, the patient lost 6 kg per day. Due to the excess of skin, the length of intensive treatment sessions was reduced to avoid the compression garment causing a tourniquet effect, the size of the compression stocking was only adjusted once per day and daily walks were included in the treatment program. After 1 month, the size of the leg was reduced by another 4 kg. Intensive lymphedema treatment is an option that rapidly reduces edema, and constant use of low-stretch compression maintains the result achieved and continues to reduce the swelling.
Keywords: elephantiasis; treatment; intensive